KEPRIBADIAN EKSTROVERT-INTROVERT DAN PEMEROLEHAN BAHASA KEDUA PERSPEKTIF PSIKOLINGUISTIK PADA SANTRI PONDOK MODERN - Ahmad Habibi Syahid (Al Qalam, 2014)
Personality as one of the factors of language acquisition in modern cottage students. Open personality (extrovert) or closed personality (introvert) has keberpengaruhan on language acquisition. Both of these personalities, extrovert and introvert has a way, the model, as well as their own style in acquiring language. Language acquisition means the ability to use language that is obtained, especially in the four language skills, such as listening skills (listening abilities), speech (speaking ability), literacy (reading ability), and writing skills (writing abilities). Language acquisition is based on a process that is not conscious (subconscious). Therefore, extrovert or introvert personality has a different way of language acquisition. This is caused by differences in personality- type. Extroverts tend to be more open, while introverts tend to be closed. This study refers to Noam Chomsky thought with his theory in his book Transforming Generative entitled "Language and Mind" which says that humans have an innate trait in acquiring a language that is inborn. Extrovert and introvert personality characteristic of the human personality. Personality is a factor that affects language acquisition. This study used, a qualitative method with descriptive analysis approach to describe the findings of extrovert and introvert personality behavior in acquiring language. This study revealed that extrovert and introvert personality has a certain way and in acquiring language models. However, there are differences in the tendency towards acquiring the four language skills. Key Words: Personality, Extrovert-Introvert, Second Language Acquisition, Pshycolinguistic, Student of Boarding School